DEVELOPMENT OF DIGITAL-BASED MARKETING STRATEGIES AND IMPLEMENTATION OF MSME LELE HUTAURUK E-MARKET PLACE WEBSITE - Evi Silvana Muchsinati; Yuliana Lenda Mea; Jose Manuel Budiman (ConCEPt - Conference on Community Engagement Project, 2022)
The Covid-19 pandemic and a lack of knowledge regards to marketing strategies can hinder business growth. Therefore, it is necessary to create a marketing strategy by utilizing technological advances in developing a business to reach wider consumers and increase sales. The method used in Community Service (PkM) activity was starting from the preparation stage, that is surveying the field to conduct observations and interviews. Community Service (PkM) activity was conducted at the Catfish MSME, Lele Hutauruk (LeHu) with aims to assist in creating digital-based marketing strategies by promoting businesses using advertisements. Advertisement in the form of images through WhatsApp and online sales with a website-based delivery order system. The results of the Community Service (PkM) activities at Lele Hutauruk (LeHu) are E-marketplace website as an online store that sells Catfish, advertisement using images for promotion through social media, and material modules on marketing strategies. The implementation of the output has succeeded in increasing sales by 5%.